Good Corporate Governance Moderation on Profitability, Capital Structure, CSR, and Firm Value in Healthcare - Iiniya Zulfasari; Hasan Mukhibad (Equity: Jurnal Ekonomi, 2026)
This study is motivated by the importance of firm value in the healthcare sector, which faces high operational risk, long-term financing needs, and increasing demands for transparency and accountability. This research aims to examine the effects of profitability, capital structure, and Corporate Social Responsibility (CSR) on firm value, as well as to analyze the moderating role of Good Corporate Governance (GCG) in Indonesian healthcare companies. A quantitative approach was employed using panel data regression and Moderated Regression Analysis (MRA), with a sample of 22 healthcare companies listed on the Indonesia Stock Exchange during the 2018–2024 period, resulting in 154 firm-year observations. The results show that profitability, measured by Return on Assets (ROA), has a positive and significant effect on firm value. Meanwhile, capital structure and CSR disclosure do not have a significant effect on firm value. The findings also reveal that GCG weakens the relationship between profitability and firm value, suggesting that investors may consider not only the level of profit generated by a company but also the quality of its governance when evaluating corporate performance. This study contributes to the corporate governance and firm value literature by providing empirical evidence on the moderating role of GCG in the relationship between financial and non-financial factors and firm value in the Indonesian healthcare sector.